1994
DOI: 10.1002/tea.3660310105
|View full text |Cite
|
Sign up to set email alerts
|

The ability to understand and use conceptual change pedagogy as a function of prior content learning experience

Abstract: This research examined the relationship between content instruction and the development of elementary teacher candidates' understanding of conceptual change pedagogy. Undergraduate students (n = 27) enrolled in two sections of a science methods course received content instruction through either traditional or conceptual change methods, followed by instruction about conceptual change pedagogy. Candidates were interviewed pre‐ and postinstruction about their content and pedagogical knowledge and also wrote conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 27 publications
2
81
1
5
Order By: Relevance
“…First, our review found-as is typically assumed-that preservice elementary teachers demonstrate unsophisticated knowledge of some specific science topics (e.g., Atwood & Atwood, 1996;Stofflett & Stoddart, 1994). Second, beginning elementary teachers tend to have unsophisticated beliefs about the nature of science (e.g., Abd-el-Khalick, 2001), again as is typically assumed, though we also noted some exceptions to this trend in the literature.…”
Section: Overcoming Challenges Through Addressing Goalssupporting
confidence: 63%
“…First, our review found-as is typically assumed-that preservice elementary teachers demonstrate unsophisticated knowledge of some specific science topics (e.g., Atwood & Atwood, 1996;Stofflett & Stoddart, 1994). Second, beginning elementary teachers tend to have unsophisticated beliefs about the nature of science (e.g., Abd-el-Khalick, 2001), again as is typically assumed, though we also noted some exceptions to this trend in the literature.…”
Section: Overcoming Challenges Through Addressing Goalssupporting
confidence: 63%
“…This emphasises the importance of relevance to the individual. It also provides a framework for designing educational programmes that has been put into practice in scientific education (Stofflett and Stoddart 1994). The PNE session, as delivered here, addressed some but not all of these steps to a greater or lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“…This elicited the question of how student teachers are taught today. After all, in order to change educational practices it is necessary 'to break the circle' (Stofflett & Stoddart, 1994) of traditionally trained teachers who teach in a traditional manner. It seems reasonable to expect that new educational practices will be introduced in teacher education.…”
Section: Introductionmentioning
confidence: 99%